Isopenicillin N synthase mediates thiolate oxidation to sulfenate in a depsipeptide substrate analogue: implications for oxygen binding and a link to nitrile hydratase? - Ge, W; Clifton, I; Stok, J; Adlington, R; Baldwin, J; Rutledge, P (2008)
Isopenicillin N synthase (IPNS) is a nonheme iron oxidase that catalyzes the central step in the biosynthesis of beta-lactam antibiotics: oxidative cyclization of the linear tripeptide delta-L-alpha-aminoadipoyl-L-cysteinyl-D-valine (ACV) to isopenicillin N (IPN). The ACV analogue delta-L-alpha-aminoadipoyl-L-cysteine (1-(S)-carboxy-2-thiomethyl)ethyl ester (ACOmC) has been synthesized as a mechanistic probe of IPNS catalysis and crystallized with the enzyme. The crystal structure of the anaerobic IPNS/Fe(II)/ACOmC complex was determined to 1.80 A resolution, revealing a highly congested active site region. By exposing these anaerobically grown crystals to high-pressure oxygen gas, an unexpected sulfenate product has been observed, complexed to iron within the IPNS active site. A mechanism is proposed for formation of the sulfenate-iron complex, and it appears that ACOmC follows a different reaction pathway at the earliest stages of its reaction with IPNS. Thus it seems that oxygen (the cosubstrate) binds in a different site to that observed in previous studies with IPNS, displacing a water ligand from iron in the process. The iron-mediated conversion of metal-bound thiolate to sulfenate has not previously been observed in crystallographic studies with IPNS. This mode of reactivity is of particular interest when considered in the context of another family of nonheme iron enzymes, the nitrile hydratases, in which post-translational oxidation of two cysteine thiolates to sulfenic and sulfinic acids is essential for enzyme activity.